PSICOLOGÍA DEL BIENESTAR INTEGRAL. ANÁLISIS Y VALORACIÓN DE TRES MODELOS COMPLEMENTARIOS. - Rodríguez Ramos, Rómulo (Medicina Naturista)
This article, based on the approach of Integral Well-being Psychology, is compared with Martin Seligman’s Positive Psychology models and Carol Rift’s Psychological Well-being model. The goal is to unify criteria among the three models, allowing for a useful approach to developing these models in psychology.